Trace element concentrations in the groundwater of the Tamiraparani river basin, South India: Insights from human health risk and multivariate statistical techniques. (October 2017) - Magesh, N.S.; Chandrasekar, N.; Elango, L.
Abstract: This study investigates the concentration of trace elements in the groundwater of Tamiraparani river basin, South India. 124 groundwater samples were collected representing diverse landuse condition over the study area. The results reveal that the mean concentrations of Fe, Mn, Cu, Cr, Pb, Zn and Ni were 0.269, 0.02, 0.007, 0.007, 0.003, 0.066, and 0.004 ppm respectively. The decreasing trend of trace element content shows the following order: Fe > Zn > Mn > Cu > Cr > Ni > Pb. Significant positive correlation (p < 0.05) is found between most of the variables such as water level and Fe, Pb; EC and Ni; Fe and Pb; Mn and Pb; Cu and Zn, Ni; Cr and Pb; Zn and Ni. The studied trace elements are found below the international drinking water guidelines except Fe, Mn, and Pb. The Empirical Bayesian Kriging (EBK) model is used to interpolate the studied metal concentrations in the groundwater of the study area. A health risk assessment was carried out using exposure dose index (CDI) and hazard quotient (HQ). The CDI values of trace elements for oral and dermal pathways shows the following order of Fe > Zn > Mn > Cu > Cr > Ni > Pb and Fe > Zn > Mn > Cr > Cu > Ni > Pb respectively. The Hazard quotients suggest that the risk of contamination through oral and dermal pathways is feeble as all the elements show values less than one. The multivariate statistical analysis reveals that the source of trace elements in the groundwater is through natural origin except copper, chromium and lead as these contaminants are derived from anthropogenic activities. Highlights: Trace elements in the groundwater of Tamiraparani river basin is modeled spatially. Elemental concentrations were compared with WHO standards. Emprical bayesian kriging was used and prediction errors were quantified. Health risk assessment was done through oral and dermal pathways. Multivariate statistical analysis were used to infer the source.